2021
DOI: 10.1021/acs.jafc.1c04255
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Functional Characterization of Multiple NADPH-Cytochrome P450 Reductase Genes from Camellia sinensis in View of Catechin Biosynthesis

Abstract: Catechins are critical constituents for the sensory quality and health-promoting benefits of tea. Cytochrome P450 monooxygenases are required for catechin biosynthesis and are dependent on NADPH-cytochrome P450 reductases (CPRs) to provide reducing equivalents for their activities. However, CPRs have not been identified in tea, and their relationship to catechin accumulation also remains unknown. Thus, three CsCPR genes were identified in this study, all of which had five CPR-related conserved domains and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Both CPR classes were reported to be able to support the in vitro activities of CYPs involved in specialized metabolism ( Rana et al., 2013 ). However, based on numerous functional analyses in planta , CPR class I was believed to be responsible for basal or constitutive metabolisms, while CPR class II was more responsible for adaptation and defense mechanisms, involving numerous specialized metabolisms ( Rana et al., 2013 ; Parage et al., 2016 ; Huang et al., 2021 ; Zou et al., 2021 ). This study showed that LjCPR1 is closely involved with CYP716A51, a C-28 oxidase, which is involved in triterpenoid biosynthesis, one of the specialized metabolisms in L. japonicus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both CPR classes were reported to be able to support the in vitro activities of CYPs involved in specialized metabolism ( Rana et al., 2013 ). However, based on numerous functional analyses in planta , CPR class I was believed to be responsible for basal or constitutive metabolisms, while CPR class II was more responsible for adaptation and defense mechanisms, involving numerous specialized metabolisms ( Rana et al., 2013 ; Parage et al., 2016 ; Huang et al., 2021 ; Zou et al., 2021 ). This study showed that LjCPR1 is closely involved with CYP716A51, a C-28 oxidase, which is involved in triterpenoid biosynthesis, one of the specialized metabolisms in L. japonicus .…”
Section: Discussionmentioning
confidence: 99%
“…CPR class I is reported to be constitutively expressed and plays a role in primary or basal constitutive metabolism, while CPR class II is inducible by environmental stimuli and is involved in defense mechanisms through plant secondary metabolism ( Parage et al., 2016 ). Different tissue expression profiles of CPR classes I and II were reported in Withania somnifera ( Rana et al., 2013 ), Panax ginseng ( Zou et al., 2021 ), Camellia sinensis ( Huang et al., 2021 ), and Catharanthus roseus ( Parage et al., 2016 ). The differences in the protein sequences and expression levels of CPR classes I and II suggest that they have different roles in plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Divergence of pharmacodynamic components in different species/varieties/strains (Qin et al, 2014;, tissues (Guo et al, 2022;Pan et al, 2022) and development stages (Huang et al, 2021;Zhang et al, 2022b) of medicinal plants implicates expression level of key proteins involved in biosynthesis and metabolism of medicinal compounds (Figure 3, yellow part). Based on quantitatively targeted subproteomic analysis of the high and low artemisinin content of sweet wormwood (Artemisia annua), the increase expression of DBR2 accounts for the high artemisinin content .…”
Section: Figurementioning
confidence: 99%
“…Transcript and metabolite profiling of stress/elicitor-treated plants or cell cultures can be used to determine gene function in secondary metabolism . CPR class II genes from W. somnifera, P. ginseng, C. sinensis, and C. roseus were highly induced by methyl jasmonate (MeJA) treatment, whereas their CPR class I genes showed less or no induction (Rana et al, 2013;Parage et al, 2016;Huang et al, 2021;Zou et al, 2021). Interestingly, this different effect of phytohormone treatment was also observed in OSCs and CYPs.…”
Section: Introductionmentioning
confidence: 98%